If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4(-1x + 14) = 76 Reorder the terms: 2x + 4(14 + -1x) = 76 2x + (14 * 4 + -1x * 4) = 76 2x + (56 + -4x) = 76 Reorder the terms: 56 + 2x + -4x = 76 Combine like terms: 2x + -4x = -2x 56 + -2x = 76 Solving 56 + -2x = 76 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + -2x = 76 + -56 Combine like terms: 56 + -56 = 0 0 + -2x = 76 + -56 -2x = 76 + -56 Combine like terms: 76 + -56 = 20 -2x = 20 Divide each side by '-2'. x = -10 Simplifying x = -10
| 11y/15-1/75=1/75 | | 8z-22=3(3z+11)z | | 2ax-ay+2bx-by= | | 279=4.5r+4.5(r+35.8) | | 5(3a-4b)= | | X^2+4x+15=12 | | -189+12x=-2x+399 | | 12x^3/((3x^2)^(1/3)) | | -66=21x-3 | | 27x+340=-284+11x | | c=15x+30000 | | (5w-2p)(3w+p-4)= | | (4+3)(12*2)= | | 3+14x=31 | | 3x+2(-3x+8)=1 | | 12x^3/(3x^2)^(1/3) | | 3n/8-n/4 | | 40=-5x-10 | | (1/10)x(2/3) | | -4x^2=-12 | | -72-16x=114-10x | | 2x-8x+3x-5x= | | x-5x+6= | | (2y-5)(5y+7)= | | 3-3*6+8= | | (1000000/x)*2=690.85 | | 3x-430=110+21x | | (1000000/Y)x2=690.85 | | 9x-54=-189 | | 3-3*6-2=0 | | 8-3x=3+8x | | 4x^2-6x=25x-35 |